The role of physical culture and health activities in harmonising the social and personal life skills of those engaged in physical culture - Chermit, K.D.; Paatova, M.E.; Naumenko, Yu.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop conceptual approaches to physical education and health activities for those engaged in physical culture in order to harmonise and correct vitality. Results and conclusions. The article establishes the most important interrelations between the concepts of ‘social and personal viability’ and ‘physical culture and recreation activities,’ necessary for designing physical culture and recreation activities based on a systematic and subjective approach to exert the most complete and widespread influence on the social and personal viability of those involved. The presented content corresponds to the research directions ‘Socio-cultural activities in the field of physical culture’ (5.8.4 ‘Physical culture and professional physical training’) and ‘Technologies of correction of physical and mental development, self-realization and socialization’ (5.8.6 ‘Health-improving and adaptive physical culture’). The article is aimed at researchers of the problem of the development of subjectivity engaged in physical culture.